EuReCa_Serbia 2014-2021 - Influence of predictors on occurrence of shockable rhythm, any ROSC, and admission ROSC in patients with EMS-witnessed OHCA (Journal Resuscitatio Balcanica, 2025)
Aims: This study aimed to identify predictors of prehospital outcomes, specifically initial shockable rhythms and return of spontaneous circulation, in out-of-hospital cardiac arrest cases witnessed by emergency medical services.Materials and Methods: The study utilized epidemiological data collected via EuReCa questionnaires from October 1, 2014, to December 31, 2021. It included patients treated by EMS, covering both pediatric cases and non-cardiac causes of cardiac arrest. Data from 16 municipalities in Serbia, representing 24.13% of the population, were analyzed using SPSS Statistics. Statistical significance was defined as p
Keywords: prehospital outcomes, initialyl shockable rhythm, ROSC, epidemiological predictors, EMS